Coherence and Collaboration in Teacher Education Reform - Russell, Tom; McPherson, Suzin; Martin, Andrea (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
Traditional teacher education programs, frequently criticized for ineffectiveness, are changing at several Canadian universities. A range of literature on reform in teacher education suggests that coherence among program elements and collaborative environments are key features of successful reforms. Using a framework of critical analysis, we examined shortcomings of traditional programs and considered some characteristics of alternative approaches, including authorizing prospective teachers’ voices and experiences, school-university collaboration, and scaffolded induction into the profession. Without direct attention to coherence in program design and delivery and collaboration among stakeholders, reform efforts seem unlikely to succeed. L’étude analyse les lacunes des programmes traditionnels de formation à l’enseignement et se penche sur certaines caractéristiques des nouvelles approches, dont la prise en compte des opinions et expériences des enseignants en formation, la collaboration entre l’université et l’école et l’encadrement des nouveaux enseignants durant leur période de probation. La cohérence entre la conception et la prestation des programmes et la collaboration entre les intéressés sont essentiels pour le succès des efforts de réforme.